Forest resource accounting: Physical accounts and monetary accounts for sugar palm in South Sulawesi, Indonesia. Issue 1 (March 2021) - Makkarennu,; Caroline, A; Supratman,
Abstract: The objective of this research is to analyze a balance sheet giving a profile of what stocks of the sugar palm (Arenga pinnata) resource are available at a given point in time and prepare an account of what uses are made of these stocks, what sources they are derived from and how they are added to or transformed over time. This study was conducted at the Bonto Sinala Village, Sinjai District, South Sulawesi. The method used in this research is resource mapping, observation, and interview. The physical accounts and monetary accounts are analyzed by calculating the number of initial reserves in the study year, plus planting then deducting the amount of depletion so that the final amount of reserves will be obtained. The results show that the final reserve of palm sugar seen from the physical balance sheet had a value of 339.360 kg and a monetary balance of IDR 9.048.933.384. The utilization of sugar palm will shrink every year if there is no sustainable management of forest products.